Performances of a portable electrospinning apparatus - Mouthuy, P; Groszkowski, L; Ye, H (Springer Nature, 2015)
To demonstrate that portable electrospinning devices can spin a wide range of polymers into submicron fibres and provide a mesh quality comparable to those produced with benchtop machines. We have designed a small, battery-operated electrospinning apparatus which enables control over the voltage and the flow rate of the polymer solution via a microcontroller. It can be used to electrospin a range of commonly used polymers including poly(ε-caprolactone), poly(p-dioxanone), poly(lactic-co-glycolic acid), poly(3-hydroxybutyrate), poly(ethylene oxide), poly(vinyl acohol) and poly(vinyl butyral). Moreover, electrospun meshes are produced with a quality comparable to a benchtop machine. We also show that the portable apparatus is able to electrospray beads and microparticles. Finally, we highlight the potential of the device for wound healing applications by demonstrating the possibility of electrospinning onto pig and human skins. Portable electrospinning devices are still at an early stage of development but they could soon become an attractive alternative to benchtop machines, in particular for uses that require mobility and a higher degree of flexibility, such as for wound healing applications.